Novel nimesulide multicomponent solid forms: screening, synthesis, thermoanalytical study and characterization - de Almeida, Amanda Cosmo [UNESP]; Ferreira, Patrícia Osório [UNESP]; Porto, Maria Vitória [UNESP]; Canotilho, João; de Castro, Ricardo António Esteves; Caires, Flávio Junior [UNESP]; da Silva Eusébio, Maria Ermelinda (Springer Nature, 2024)
Nimesulide (NMS) is a widely used non-steroidal anti-inflammatory drug, however, presents low aqueous solubility. One way to overcome the solubility issue of drugs is altering their solid forms through some approaches like cocrystals, coamorphous, and eutectic mixtures. The purpose of this work was to prospect new multicomponent solid forms of NMS. A virtual-experimental cocrystal screening was carried out through COSMOquick software and mechanochemical experiments. Alternatively, dual-drug coamorphous systems were investigated by quench cooling and/or cryomilling processes. All solid samples were characterized using differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD) and infrared spectroscopy (FTIR). The results confirmed the successful synthesis of a NMS-piperazine cocrystal (NMS-PPZ), two new eutectic mixtures NMS-gentisic acid (NMS-GSA) and NMS-isoniazid (NMS-INH), as well as novel drug-drug coamorphous systems. The eutectic compositions were determined by binary solid–liquid phase diagram construction and Tamman’s triangle plot. Nimesulide-omeprazole (NMS-OMP) coamorphous system was found to be stable for at least 120 days in dry conditions. The coamorphous system with bicalutamide (NMS-BICA) prepared by quench cooling process is more stable than that obtained by cryomilling. Finally, the dissolution rate study demonstrated that NMS multicomponent systems are dissolved relatively faster than pure drug.
Keywords: Dissolution rate study; Dual-drug solid systems; Non-steroidal anti-inflammatory drug; Thermal analysis; Virtual-experimental screening